PERILAKU CUCI TANGAN DI KALANGAN SISWA-SISWI SMAK SANTA AGNES SURABAYA - Eka Cipta Halim; Oedojo Soedirham (The Indonesian Journal of Public Health, 2018)
Cleanliness is a state free of dirt, including dust, garbage and odors. Hygiene is also a lifestyle, and is also included in Clean and Healthy Lifestyle. Student always consumption of food after exercise can restore lost of body stamina. However, student often forget the Wash the Hand with Soap before eating food. Behavioral factors consist of supporting factors, enabling factors and strengthening factors. This purpose of study in order to know the knowledge, attitude and behavior of informants. The research was done at High School of Santa Agnes Surabaya by using descriptive method of qualitative approach. Instrument in this research is guidance of deep interview with informant amounted to 8 people. The variables in this study were the students' knowledge, the attitude of the students and the behavior of the students associated with the CTPS. Supporting factors consist of attitude and behavioral knowledge. Knowledge of students was in the low knowledge, because only limited to know. Attitudes toward the behavior of CTPS at SMAK Santa Agnes support CTPS as a beneficial healthy behavior. The behavior of CTPS at SMAK Santa Agnes was lacking, especially after sports. Possible factors in the form of facilities that have been good, but the number is still inadequate. The reinforcing factor of the teacher's encouragement to perform the CTPS and the motivation of the dirty hand-related sectional environment can lead to ill experiences of illness that have been experienced and are accustomed to CTPS. The conclusion that can be drawn is that all informants have diverse behavior and risk to their health. Lazy behavior is the main key that must be resisted so as not to interfere with health.